1998
DOI: 10.1029/97ja01660
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of global ionospheric responses to intense magnetic storm conditions

Abstract: Abstract. We report on a study of three intense ionospheric storms that occurred in September 1989. Using Dst as a reference for storm onset and subsequent main and recovery phases, we analyze the observed worldwide responses of F region heights hmF 2 and densities NmF 2 as a function of universal and local times, latitudinal domains, and storm onset-times; and we compare the characteristics of all three storms. The following points are among the major findings: (1) The negative phase storm was the dominant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 44 publications
7
52
0
5
Order By: Relevance
“…Within the last few years, it was well confirmed that positive storm effects are also observed in the night-side hemisphere (Oliver and Hagan, 1991;Burnside et al, 1991;Szuszczewicz et al, 1998;Tsagouri et al, 2000;Belehaki and Tsagouri, 2002). They are also predicted by numerical simulations (Mansilla and Manzano, 1998) and many responsible mechanisms have been occasionally proposed.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Within the last few years, it was well confirmed that positive storm effects are also observed in the night-side hemisphere (Oliver and Hagan, 1991;Burnside et al, 1991;Szuszczewicz et al, 1998;Tsagouri et al, 2000;Belehaki and Tsagouri, 2002). They are also predicted by numerical simulations (Mansilla and Manzano, 1998) and many responsible mechanisms have been occasionally proposed.…”
Section: Introductionmentioning
confidence: 53%
“…They also maintain that if a positive phase is driven by winds before dusk, it will rotate into the nightside and nighttime positive effects of this type have been observed (Szuszczewicz et al, 1998;Tsagouri et al, 2000). However, the understanding of positive phase observations is not always so simple, such as in cases of nighttime initiated positive effects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations